Analysis of the producers’ demographic and socioeconomic characteristics that impact on the access to agricultural extension services in Mozambique (Research, Society and Development, 2022)
In the last few decades, the agricultural extension services in Mozambique have been focused mainly on the training and strengthening of producer associations, improved technology transfer, and technical assistance. This study aimed to establish the demographic and socioeconomic characteristics of the producers which impact the access to agricultural extension services. In methodological terms, a logistic regression model was estimated and the variables used were provided by 2010 Agricultural and Livestock Census, also known as CAP- (Portuguese acronym for Censo Agropecuário de 2010). Results showed that despite the universal character of the agricultural extension policy, the distribution of access to these services was very uneven, in terms of variables such as gender and age of the household head, education levels, ability to read, and technology use (irrigation, fertilizers, and pesticides). This information is highly relevant to decision-making, as it can guide future improvements in the services, both in terms of coverage and of quality of the technical assistance.